2021
DOI: 10.3389/fpubh.2021.623441
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Occupational Health and Safety Training for Chinese Construction Workers Based on the CHAID Decision Tree

Abstract: Background: Occupational health and safety (OHS) training is an important way to prevent construction safety risks. However, the effectiveness of OHS training in China is questionable. In this study, the CHAID (chi-squared automatic interaction detection) decision tree, chi-square analysis, and correlation analysis were used to explore the main, secondary, weak, unrelated, and expectation factors affecting the effectiveness of training. It is the first to put forward the “five-factor method” of training effect… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
11
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 14 publications
(14 citation statements)
references
References 58 publications
(55 reference statements)
1
11
0
Order By: Relevance
“…Thus, the findings of that health and safety training for construction workers is essential for their safety at the construction site needed for safety, hazard management and emergency procedures for safety management is upheld by this study. Furthermore, Taylor et al 22 and Cao et al 8 found that if general health and safety policies are to be incorporated into specific job practices and skill levels are to be raised to an acceptable standard, training is required, further corroborated by this findings study.…”
Section: Discussion Of Resultssupporting
confidence: 75%
See 1 more Smart Citation
“…Thus, the findings of that health and safety training for construction workers is essential for their safety at the construction site needed for safety, hazard management and emergency procedures for safety management is upheld by this study. Furthermore, Taylor et al 22 and Cao et al 8 found that if general health and safety policies are to be incorporated into specific job practices and skill levels are to be raised to an acceptable standard, training is required, further corroborated by this findings study.…”
Section: Discussion Of Resultssupporting
confidence: 75%
“…Additionally, due to competing political, social and economic interests, OHS issues are mostly neglected in most African countries. 7 , 8 The effect of poor or lack of occupational health and safety policies in organisations in Africa is mostly deaths, permanent disabilities, severe injuries and absenteeism. One of Africa’s key sectors or industries closely associated with health and safety issues is the construction industry.…”
Section: Introductionmentioning
confidence: 99%
“…The categories of each independent variable were merged if they were not significantly different from the dependent variable and the cutoff values are established automatically by the chisquare test results. [27][28][29][30][31] Furthermore, we add and express it in other words by the explanation of CHAID model from other precedence articles, the CHAID algorithm is a nonparametric procedure and, therefore, it required no assumptions to be made of the underlying data. Also, CHAID treats the entire system and user-missing values for each independent variable as a single category.…”
Section: Discussionmentioning
confidence: 99%
“…Methodologically wise, following a critical review of existing relevant studies [78,[97][98][99][100][101], an online questionnaire was developed and administered using Google Forms as the main tool, an approach in accordance with the practice used widely [102][103][104][105][106]. The questionnaire was developed adapting the 'Safety Culture Questionarrie', used by the University of Aegean in a relevant study [100], as well as previous work on factors affecting the level of awareness regarding OSH [66,[107][108][109][110]. Ultimately, a 19-item questionnaire was developed.…”
Section: Methodsmentioning
confidence: 99%